Development of a Low-cost Simulator ORISIM (ORIF and OREF Simulator) as a Wound Care Learning Medium - Tiana Rachmadita; Auridsa Nihlahani; Tri Johan Agus Agus Yuswanto (FORIKES, 2026)
Postoperative wound care for Open Reduction Internal Fixation (ORIF) and Open Reduction External Fixation (OREF) is a core competency in medical–surgical nursing. However, access to task‑specific and affordable simulators remains limited, particularly in low‑resource educational settings. Low‑cost simulation models have been shown to enhance clinical skill acquisition and self‑efficacy among nursing students, yet challenges related to anatomical fidelity and wound realism persist in many existing models. This study aimed to develop and evaluate ORISIM, a low‑cost, context‑specific wound‑care simulator designed for ORIF and OREF postoperative conditions, and to assess its feasibility, usability, and educational value in nursing skills training. This research employed a Research and Development (R&D) design consisting of five phases: needs identification, prototype design and construction, expert validation, model revision, and preliminary testing. Three experts participated in the validation process: one orthotics–prosthetics specialist and two wound‑care nursing practitioners. Preliminary testing involved 20 undergraduate nursing students who had completed theoretical and demonstrative instruction on wound care. Quantitative data were collected using a modified Michigan Standard Simulation Experience Scale (MiSSES), while qualitative feedback was analyzed thematically. Expert validation indicated that ORISIM was feasible for educational use, with recommendations for improving anatomical fidelity and wound realism. Quantitative findings showed high levels of student acceptance across all MiSSES domains, with mean scores of 4.17 for self‑efficacy, 4.23 for educational value, and 4.10 for simulation realism. Students reported increased confidence in performing wound‑care procedures and highlighted the simulator’s usability and durability. Qualitative analysis produced three themes: wound realism, material characteristics, and educational value with ease of use. Although some students noted limitations in anatomical detail and material elasticity, ORISIM was widely regarded as beneficial for structured and repetitive skills practice. In conclusion, ORISIM demonstrates strong potential as a cost‑effective and educationally relevant simulator for ORIF and OREF wound‑care training. While improvements in anatomical fidelity are warranted, the model effectively enhances students’ self‑efficacy and supports foundational clinical skill development. Future research should incorporate experimental or quasi‑experimental designs to further evaluate ORISIM’s effectiveness and compare its performance with commercial simulators.Keywords: wound‑care simulation; nursing education; low‑cost simulator; clinical skills training; self‑efficacy